2010
DOI: 10.1097/qai.0b013e3181ef4963
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Down-Regulates Innate Antiviral Response Genes in Patients With AIDS in Sub-Saharan Africa

Abstract: Objective HIV pathogenesis is characterized by destructive imbalances between virus-mediated immune damage, anti-viral immune responses, and immune activation. We characterized the effects of successful antiretroviral therapy (ART) to identify the breadth and patterns of HIV-associated gene expression. Methods In a prospective observational, longitudinal cohort study of 10 ART-naive Ugandans with AIDS (median 30 CD4+/μL), we measured mRNA gene profiles in peripheral blood using Affymetrix U133_Plus2.0 microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 59 publications
5
23
0
Order By: Relevance
“…We detected increased expression of A3G in acute infection in oral and blood samples, which persisted in untreated infection but remained at control levels in ART-treated animals. A study examining ART-responsive genes in HIV infected individuals also showed that CXCL10 and A3G expression is abrogated after successful ART 57 .…”
Section: Discussionmentioning
confidence: 99%
“…We detected increased expression of A3G in acute infection in oral and blood samples, which persisted in untreated infection but remained at control levels in ART-treated animals. A study examining ART-responsive genes in HIV infected individuals also showed that CXCL10 and A3G expression is abrogated after successful ART 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Antiretroviral therapy (ART) exposure in utero and in the perinatal period may also impact immune development. In adults, ART is associated with anemia, neutropenia, relative lymphopenia and down regulation of select pattern recognition receptor genes 39-42 . However, there are currently no data measuring the effect of ART exposure on functional innate immune ontogeny early in life.…”
Section: Discussionmentioning
confidence: 99%
“…From May 2006 until December 2013, HIV-infected persons with CD4<200 cells/ μ l who had either no active opportunistic infection at time of initiating ART or cryptococcal meningitis were enrolled as described previously. 1216 Cryptococcal meningitis was diagnosed by cerebrospinal fluid (CSF) cryptococcal antigen (IMMY Inc., Norman OK) and/or quantitative fungal culture. 13,14 The IMMY Inc. latex agglutination text was used prior to 2012, whereas the LFA was used after this point.…”
Section: Methodsmentioning
confidence: 99%